2020
DOI: 10.1080/20002297.2020.1742523
|View full text |Cite
|
Sign up to set email alerts
|

Innovative application of nested PCR for detection of Porphyromonas gingivalis in human highly calcified atherothrombotic plaques

Abstract: Atherothrombosis, leading to stroke and myocardial infarction, is responsible for most of the deaths in the world. An increased risk of atherothrombotic vascular events has been reported in patients with periodontitis. Periodontitis is a chronic multifactorial inflammatory disease, which involves a dysbiotic microbiota, and leads to a progressive destruction of the tooth-supporting apparatus. Transcient periodontal pathogen blood translocation, mainly bacteremia, has been associated with the severity of gingiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…P. gingivalis can invade and colonize the patient’s atherosclerotic plaque. 141 Chiu et al analyzed the microorganisms in carotid endarterectomy specimens of 76 cardiovascular patients and found that the positive detection rate of P. gingivalis was 42%. 142 And it was also detected other periodontal pathogens in atherosclerotic plaques, such as A. actinomycetemcomitans and T. forsythia .…”
Section: Oral Microbes and Cardiovascular Diseasesmentioning
confidence: 99%
“…P. gingivalis can invade and colonize the patient’s atherosclerotic plaque. 141 Chiu et al analyzed the microorganisms in carotid endarterectomy specimens of 76 cardiovascular patients and found that the positive detection rate of P. gingivalis was 42%. 142 And it was also detected other periodontal pathogens in atherosclerotic plaques, such as A. actinomycetemcomitans and T. forsythia .…”
Section: Oral Microbes and Cardiovascular Diseasesmentioning
confidence: 99%
“…Periodontitis has effects on the endothelial function, causing endothelial dysfunction, stiffness of the arteries and high BP [ 98 ], and hypertension-associated oral pathogens (HOP) as C. rectus , V. parvula , P. melaninogenica have been identified [ 99 ]. Late colonizers as P. gingivalis , A. actinomycetemconcomitan , T. forsythia, and T. denticola have been explored in vascular atherosclerosis lesions but their possible association with blood pressure has not been evaluated [ 100 , 101 ]. Hypertension, such as periodontitis, is considered a low-grade inflammatory disorder and it is marked by the presence of pro-inflammatory cytokines [ 102 ].…”
Section: Periodontitis Affects Hypertension (Ht)mentioning
confidence: 99%
“…In recent years, the effect of Pg in the progress of AS has been confirmed by a large number of studies. Multiple studies have employed polymerase chain reaction (PCR) to examine bacterial presence in human arterial tissues, and Pg is among the predominant bacteria frequently detected in atherosclerotic plaques [ 46 , 52 , 53 , 54 ]. Adrian Brun’s group utilized a combined approach of nested PCR and real-time PCR to successfully identify Pg with high specificity in highly calcified AS plaques of humans [ 54 ].…”
Section: Porphyromonas Gingivalismentioning
confidence: 99%
“…Multiple studies have employed polymerase chain reaction (PCR) to examine bacterial presence in human arterial tissues, and Pg is among the predominant bacteria frequently detected in atherosclerotic plaques [ 46 , 52 , 53 , 54 ]. Adrian Brun’s group utilized a combined approach of nested PCR and real-time PCR to successfully identify Pg with high specificity in highly calcified AS plaques of humans [ 54 ]. In patients with AS, the serum concentrations of IgG targeting Pg and Pg -heat shock protein (HSP) 60 are higher than in healthy individuals [ 55 ].…”
Section: Porphyromonas Gingivalismentioning
confidence: 99%